Canada's political choices restrain vaccine equity: The Bolivia-Biolyse case - Muhammad Zaheer Abbas (South Centre, 2021)
The COVID-19 pandemic has already claimed more than 4.6 million lives and caused significant economic harm. The Coronavirus is still circulating to cause further damage. In this context, this research paper argues that Canada's political choices have restrained the equitable distribution of COVID-19 vaccines. Part I evaluates Canada's nationalistic approach of procuring COVID-19 vaccines more than its needs through secretly concluded pre-purchase agreements with brand-name pharmaceutical corporations as advised by a secretly born task force having clear ties with the vaccine industry. Part II examines Canada's wavering and non-committal position on the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) Waiver proposal. Canada's confusing position of "not blocking" the TRIPS Waiver while not supporting it either lacks legal clarity. Part III analyses the Bolivia-Biolyse case which highlights clear contradictions between statements and actions of the Canadian government. Since March 2021, Biolyse Pharma has been hamstrung by the first step in Canada's Access to Medicines Regime (CAMR), where a preliminary requirement is that the COVID-19 vaccine must be added to Schedule 1 of the Canadian federal Patent Act before applying for an export-oriented compulsory licence. The Bolivia-Biolyse case is important as a test case for the CAMR system. Workability of this export-oriented compulsory licensing regime is critical for low- and middle-income countries in the Global South lacking the domestic capacity to manufacture COVID-19 vaccines. The Bolivia-Biolyse case is also important as Canada has argued at the World Trade Organization (WTO) that the TRIPS Waiver is not required because the existing mechanisms are working as intended.
Keywords: 300